Dreaming the Nation: René Marqués's Los soles truncos - Vargas, Margarita (Latin American Theatre Review, 2004)
Marqués's politics and Los soles truncos reveal that his ideal nation was male-centered. He creates a tripartite piece with three characters as metaphors of Puerto Rico’s three political parties. To attain independence, the old system must be razed so that out of its ashes a new sun/family/nation can be born (MV).